Soy and wheat fibers usage in wheat bread production - Shydlovska, Olena; Medvid, Irina; Balyas, Natalia (My University, 2016)
Сonsidered the feasibility of soy and wheat fibers usage in wheat bread production
Keywords: харчові волокна; пищевые волокна; dietary fibers; соєва клітковина; соевая клетчатка; soy fibers; пшенична клітковина; пшеничная клетчатка; wheat fibers; кафедра готельно-ресторанної справи